HABITUS AND AGENT IN LITERATURE PRACTICE ACTIVITIES IN JAMBI CITY IN THE AiR THEATER COMMUNITY (ART IN REVOLT) - Pratiwi, Retno Endah; ivan, ivan adilla; zurmailis, Zurmailis (Magistra Andalusia: Jurnal Ilmu Sastra, 2023)
AbstractThe literary community has an important role in activating literary practice in a social environment. The literary activity carried out by these communities is engaged in the promotion of the literary genres of poetry and theater or drama. The purpose of this study is to show how a community becomes important and also a source of vital literary creation for various existing literary genres, be it poetry, prose, or drama. The method used in this study is the method described by Pierre Bourdieu in his theory, namely genetic structuralism. The agents within this community are tasked with developing and carrying out these literary creation practices. The AiR Theater Community, with its agents, carries out literary activities in the City of Jambi by developing a literary life in the form of poetry, prose, and also theater which the people of Jambi City can witness and participate in. Thus, the existing literary climate is expanding with activities built by agents who move continuously to activate existing literary programs in the community.Keywords: literature community, agent, Pierre bourdieu